2023
DOI: 10.1038/s41380-023-02310-w
|View full text |Cite
|
Sign up to set email alerts
|

Trans-ancestry epigenome-wide association meta-analysis of DNA methylation with lifetime cannabis use

Fang Fang,
Bryan Quach,
Kaitlyn G. Lawrence
et al.

Abstract: Cannabis is widely used worldwide, yet its links to health outcomes are not fully understood. DNA methylation can serve as a mediator to link environmental exposures to health outcomes. We conducted an epigenome-wide association study (EWAS) of peripheral blood-based DNA methylation and lifetime cannabis use (ever vs. never) in a meta-analysis including 9436 participants (7795 European and 1641 African ancestry) from seven cohorts. Accounting for effects of cigarette smoking, our trans-ancestry EWAS meta-analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…Thus, DNAm variation at this locus may plausibly reflect individual differences in immunological tolerance of cigarette smoke and, consequently, maintenance of smoking behavior. Interestingly, these CpGs were significantly associated with neither cannabis use 7 nor alcohol consumption 6 in recent large-scale EWASs. Notably, though, both these studies reported DNAm associations conditional on cigarette smoking, making them unsuitable for gauging whether the CpGs with putative effects on smoking liability are also associated with other substances.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Thus, DNAm variation at this locus may plausibly reflect individual differences in immunological tolerance of cigarette smoke and, consequently, maintenance of smoking behavior. Interestingly, these CpGs were significantly associated with neither cannabis use 7 nor alcohol consumption 6 in recent large-scale EWASs. Notably, though, both these studies reported DNAm associations conditional on cigarette smoking, making them unsuitable for gauging whether the CpGs with putative effects on smoking liability are also associated with other substances.…”
Section: Discussionmentioning
confidence: 93%
“…If so, it may be prudent to report supplementary EWAS results without smoking as a covariate, as some CpGs may have a reverse or bidirectional causal relationship with smoking. Note that the EWAS of cannabis use 7 did perform such preliminary analyses but only reported the results conditional on cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations